The personal benefits of musicking for people living with dementia: a thematic synthesis of the qualitative literature. Issue 3 (2nd September 2018) - Dowlen, Robyn; Keady, John; Milligan, Christine; Swarbrick, Caroline; Ponsillo, Nick; Geddes, Lucy; Riley, Bob
Abstract: This review aimed to explore the psychological, social and emotional benefits of music activities for people living with dementia through a systematic review of qualitative literature. Eighteen studies were identified that covered a wide range of music programmes for people with dementia, with the majority of programmes focusing on active musical participation. A thematic synthesis revealed four key benefits of music engagement for people with dementia, namely: Taking Part, Being Connected, Affirming Identity and Immersion "in the moment". Overall, engaging with music was seen to have a number of psychological, social and emotional benefits for people with dementia. However, only seven studies actively included people with dementia in the research process. Going forward, it would appear essential that people with dementia are encouraged to take a more active role in research exploring musical experiences and that a heightened emphasis is placed upon participatory approaches to knowledge generation.